2017
DOI: 10.5860/crl.78.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Roles: Canadian Academic Librarians Embedded in Faculty Research Projects

Abstract: Academic librarians have always played an important role in providing research services and research-skills development to faculty in higher education. But that role is evolving to include the academic librarian as a unique and necessary research partner, practitioner, and participant in collaborative, grant-funded research projects. This article describes how a selected sample of Canadian academic librarians became embedded in faculty research projects and describes their experiences of participating in resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There was evidence that results of this project infl uenced library work in a positive way although authors concluded that there is a need for systematic procedures which strengthen this, otherwise accidental, kind of cooperation. Embedded librarianship also interested researchers from Canada (Bedi & Walde, 2017). Their study showed that librarians taking part in primary research may offer essential contribution to entire research process.…”
Section: Research Support: Practicesmentioning
confidence: 99%
“…There was evidence that results of this project infl uenced library work in a positive way although authors concluded that there is a need for systematic procedures which strengthen this, otherwise accidental, kind of cooperation. Embedded librarianship also interested researchers from Canada (Bedi & Walde, 2017). Their study showed that librarians taking part in primary research may offer essential contribution to entire research process.…”
Section: Research Support: Practicesmentioning
confidence: 99%
“…These approaches contribute to researchers' increased understanding and better management of the research life cycle and to maximising potential research impact, thus providing a tangible value-add to researchers. This has provided a basis for librarians to transition to full partners in research collaborations (Bedi & Walde, 2017).…”
Section: Traditional Intra-university Collaborationsmentioning
confidence: 99%
“…This theme emerged in a subsequent research paper I wrote with my UVic Libraries' colleague Shailoo Bedi, published in 2017 by College & Research Libraries and entitled "Transforming Roles: Canadian Academic Librarians Embedded in Faculty Research Projects." 3 In our research, Bedi and I discovered that a librarian's involvement with grants is not only a critical path to engagement with faculty, but it also acts as a catalyst to the development and advancement of an academic librarian's own research practise. This was certainly true for me, since my involvement in Ross's research has resulted in a fruitful scholarly output, recently culminating in a chapter-length article on ontology development in Doing More Digital Humanities 4 with my fellow collaborators, Jana Millar-Usiskin and Caroline Winter.…”
mentioning
confidence: 93%